The power of design product innovation in sustainable energy technologies - Reinders, Angele; Diehl, Jan Carel; Brezet, Han. (Hoboken, N.J. : Wiley, 2012)
"Unique in linking sustainable energy technologies with innovation and product design, this book offers clear explanation of both and case studies enabling readers to understand and design energy-efficient products in several different markets.The book integrates the subject areas that are necessary for the design of sustainable and energy-efficient products based on sustainable energy technologies. The theory provided is illustrated by cases of design projects and concepts in practice. With the book's methodological approach, the reader is able to apply the information and examples in their research projects or product design processes.This book fills a void in existing literature at the intersection of innovation processes, sustainable energy technologies, energy demand reduction, product development, and user behaviour, which requires an integrated view on the development of sustainable energy solutions. As such, the editors offer a unique publication in "product innovation in sustainable energy technologies and energy-efficiency" that corresponds to the growing interest in the field"--
0
Includes bibliographical references and index.
Keywords: New products -- Environmental aspects; Product design; Green products; TECHNOLOGY & ENGINEERING / Power Resources / General